Calibration of high flow rate thoracic-size selective samplers. Issue 6 (2nd June 2016) - Lee, Taekhee; Thorpe, Andrew; Cauda, Emanuele; Harper, Martin
ABSTRACT: High flow rate respirable size selective samplers, GK4.126 and FSP10 cyclones, were calibrated for thoracic-size selective sampling in two different laboratories. The National Institute for Occupational Safety and Health (NIOSH) utilized monodisperse ammonium fluorescein particles and scanning electron microscopy to determine the aerodynamic particle size of the monodisperse aerosol. Fluorescein intensity was measured to determine sampling efficiencies of the cyclones. The Health Safety and Laboratory (HSL) utilized a real time particle sizing instrument (Aerodynamic Particle Sizer) and polydisperse glass sphere particles and particle size distributions between the cyclone and reference sampler were compared. Sampling efficiency of the cyclones were compared to the thoracic convention defined by the American Conference of Governmental Industrial Hygienists (ACGIH)/Comité Européen de Normalisation (CEN)/International Standards Organization (ISO). The GK4.126 cyclone showed minimum bias compared to the thoracic convention at flow rates of 3.5 l min −1 (NIOSH) and 2.7–3.3 l min −1 (HSL) and the difference may be from the use of different test systems. In order to collect the most dust and reduce the limit of detection, HSL suggested using the upper end in range (3.3 l min −1 ). A flow rate of 3.4 l min −1 would be a reasonable compromise, pending confirmation in other laboratories. The FSP10 cyclone showed minimum bias at the flow rate of 4.0 l min −1 in the NIOSH laboratory test. The high flow rate thoracic-size selective samplers might be used for higher sample mass collection in order to meet analytical limits of quantification.